2005
DOI: 10.1111/j.1464-410x.2005.05829.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observations of the effect of antidiuretic hormone on nocturia in elderly men

Abstract: or anticholinergics, e.g. oxybutynin, tolterodine, and propantheline bromide. We assessed the effect of desmopressin using a quantitative nocturia score and analysed its synergistic effect with α -blockers. RESULTSThe mean frequency of nocturia was 6.1 before desmopressin and most (86%) patients had an improvement in nocturia within 1-12 weeks of treatment with desmopressin. There was a 43% reduction in nocturia after using desmopressin ( P < 0.001). The correlation coefficient between the number of nocturnal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…A 43% significant reduction in nocturia was reported after using desmopressin alone ( P < 0.001) [11] . The more severe the nocturia was, the more effective the results with desmopressin, with a 0.756 correlation coefficient between the number of nocturnal voids and the reduction in nocturia after desmopressin treatment.…”
Section: Resultsmentioning
confidence: 95%
“…A 43% significant reduction in nocturia was reported after using desmopressin alone ( P < 0.001) [11] . The more severe the nocturia was, the more effective the results with desmopressin, with a 0.756 correlation coefficient between the number of nocturnal voids and the reduction in nocturia after desmopressin treatment.…”
Section: Resultsmentioning
confidence: 95%
“…Researches for desmopressin response in nocturia without NP are also scarce and debatable. Ho et al had reported a short‐term and small patient population which demonstrated desmopressin to be an effective alternative in nocturia without NP refractory to antimuscarinics . Our report with more study population revealed that desmopressin was statistically effective in reducing nocturnal voids in both groups in a longer treatment period (22.28 ± 13.32 months in non‐NP, 23.95 ± 14.80 months in NP).…”
Section: Discussionmentioning
confidence: 99%